Improving assessment and management of pain in hemophilia: an Italian Delphi consensus statement. (January 2022) - Santoro, Cristina; Di Minno, Matteo Nicola Dario; Corcione, Antonio; Di Minno, Giovanni; Martinelli, Marco; Mancuso, Maria Elisa; Acone, Benedetto; Molinari, Angelo Claudio; Passeri, Emilio Valter; Rocino, Angiola; Santoro, Rita Carlotta; Tagliaferri, Annarita; et al.
Abstract: Comprehensive evidence-based guidelines and well-validated assessment scales for pain in people with hemophilia (PwH) are needed. Here, we report 28 statements covering five topics on pain assessment and management in pediatric and adult PwH that were developed by 60 Italian hemophilia specialists during a Delphi consensus process. Overall, a clear consensus was achieved for 19 of the 28 statements. Consensus was reached on all statements on the topic of pain assessment and quality of life (QoL), including the need for regular pain assessment on a quantitative scale, the importance of distinguishing between different pain types, and the need to evaluate the impact of pain on patient QoL. The other four topics concerned acute and chronic pain management in adults and in children. Consensus was reached on statements regarding non-pharmacologic treatment and the use of first-line paracetamol (acetaminophen). There was a lack of consensus regarding the use of non-steroidal anti-inflammatory drugs, cyclooxygenase-2 inhibitors, or opioids. Highlights: Italian specialists in haemophilia care achieved a consensus on 19 of 28 statements about pain management in hemophilia. Pain needs to be investigated at each visit to the haematologist by means of a validated, quantitative tool. Acute and chronic pain represent different clinical scenarios to be treated in the frame of an individualized approach.